Insignificant impact of the presence of lactose impurity on formation and colloid stabilising properties of whey protein–maltodextrin conjugates prepared via Maillard reactions. (April 2017) - Ding, Rui; Valicka, Erika; Akhtar, Mahmood; Ettelaie, Rammile
Graphical abstract: Abstract: We investigate the sensitivity of steric stabilising properties of protein–polysaccharide conjugates, prepared via the Maillard reactions, to the presence of sugar impurity during synthesis. The sugar can also react with protein, thus rendering potential sites on protein unavailable for linkage with polysaccharide and severely reducing the efficiency of producing these types of food dispersants. We demonstrate that despite the presence of a relatively high molar ratio of lactose contaminant to maltodextrin (10:1), the covalent complexes between maltodextrin DE19 (MD19) and Whey Protein Isolate (WPI) are still formed and continue to show superior emulsifying and colloid stabilising properties compared to native protein. The improvement was particularly marked under unfavourable environmental conditions, such as pH ∼ pI of protein, up to a storage time of 21 days. In contrast, the covalent complexes of lactose + WPI were found to have rather poor emulsion stabilising characteristics, under the same conditions. We also confirm this result by performing theoretical Self Consistent Field type calculations. The stability of emulsions was monitored using a variety of measures including the average droplet size (ADS), droplet-size distribution (DSD), rheological flow behaviours and confocal laser imaging microscopy. The suggestion that the WPI-MD19 (1:2, w/w) system is quite tolerant to the presence of lactose is of significance in future large scale industrial manufacturing of such food dispersants, due to less stringent requirements for the purity of raw material (WPI).